Investigating Some Reasons and Contexts for Changing Poets' Pen Names - Majid Mansoori; raheleh maghsoodi (تاریخ ادبیات)
In Persian literary history, many readers of Persian poetry and even those contemporary with old and new poets have not often known the correct and real name of many poets and most poets have been known by their pen names or nom de plumes. Therefore, the poets have always tried scrupulously to choose the most beautiful and appropriate pen names with utmost precision; this is why some poets, due to various reasons, realized after a while that they needed to change their pen names. It must be noted that changing pen names has had a tremendous impact on the formation and durability of the poets' poetry; That is, when a poet with an old pen name had provided a name for himself, and that pen name was the best choice for his poems, there was a possibility that by changing his pen name, he would face many problems in keeping the durability of his poems. In this research, some reasons for changing poets' pen names were analyzed descriptively and analytically and it was shown that changing poets' pen names, as a literary tradition, is influenced by political, social, literal, and individual characteristics among others. Meanwhile, some poets, while choosing new pen names, did not abandon their previous pen names, and some others have replaced their old pen names with the new pen names in their old poems, and still others did not stick to the new pen names either - sometimes using the previous pen names again and sometimes newer ones. All these cases are investigable separately for each poet.